Human rights education in indonesian higher education institutions: opinions of students and teachers - Aloysia Vira Herawati; Dmitry Sergeevich Ermakov (LPMPP Universitas Negeri Yogyakarta, 2022)
As problems of intolerance and disrespect of human rights escalate in this modern world, raising public awareness on human rights is considered an inevitable task for all. Intervention of promoting human rights in education field is believed to be playing an important role to address the problems. This study wants to collect information from its research subjects on the extent to which topics of human rights are being learned and taught in higher education institutions, and on the degree of effectiveness of different methods used to learn and teach human rights in higher education institutions, as to develop human rights knowledge and understanding of students. This study uses the technique of homogenous purposive sampling to determine the research subject. The research subjects are (1) students who take the course subject of Human Rights or Citizenship and (2) lecturers who teach either the course subject of Human Rights or Citizenship, in any higher education institutions in Indonesia. The questionnaire is developed using Google Form, and is distributed online. As the result of the survey for 445 students and 72 teachers of Indonesian higher educational institutions, most of them are familiar with the concept of human rights. The most significant sources of information on human rights are university lecturers, mass media, official documents, and publications. The most important level of education to receive knowledge and build understanding on human rights are secondary education, higher education, elementary education, and vocational education. General human rights, right to freedom of religion and belief, and right to education are fully developed. More of other rights, such as rights of lesbian, gay, bisexual, transgender, and queer (LGBTQ), rights of migrants, rights of internally displaced persons, and rights of the poor, are expected to be more developed than they are now. The most effective methods are field visit/excursions, watching films, problem solving, and case studies. The least effective methods are arts (drawing and singing), writing essays and stories, and games.